FRI0190 CDAI is a predictor of physical function and bone destruction at week 52 in RA patients. (23rd January 2014) - Hanami, K.; Saito, K.; Tasaka, H.; Tanaka, Y.
Abstract : Background: Although American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) developed a new definition of remission in rheumatoid arthritis (RA) in 2010, it was based on data in RA patients treated with methotrexate (MTX) and TNF inhibitors. Objectives: We attempted to evaluate the predictive validity of the new remission criteria from tocilizumab (TCZ) data obtained in a daily clinical practice. Methods: One-hundred fifty-five RA patients who inadequately responded to prior MTX and anti-TNF inhibitor were treated with 8mg/kg of TCZ every 4 weeks in our institute. Data were analyzed from 61 patients whose physical function and progression of joint damage were evaluated at week 52 after introduction of TCZ. 28-joint Disease Activity Score (DAS28), Clinical Disease Activity Index (CDAI), Health Assessment Questionnaire (HAQ), modified total Sharp score (mTSS) were assessed by the LOCF method at 0, 24 and 52 weeks after TCZ treatment. Results: Among 61 RA patients, the mean age of the enrolled patients was 61.4 (20-84) years, disease duration was 12.8 years (0.3-40), 34 patients (55.7%) had received TNF-inhibitors, and during the study 59.0% of the patients received concomitant MTX. At baseline, almost all patients had high disease activity, mean DAS28 was 6.2±1.2 and mean CDAI was 29.7±14.0. DAS28 and CDAI were improved to 3.1±1.5 and 12.0±9.8, respectively, at week 52. 42.6% and 14.8% achieved DAS28<2.6 (DAS remission) and CDAI remission (≤2.8), respectively. The mean estimated yearly progression of mTSS was reduced from 19.7 to 0.2 after treatment with TCZ at week 52. HAQ also improved 1.55 at week 52 from 1.71 at baseline. HAQ and radiological remission rates were 16.3% and 79.0%, respectively.When a good outcome was defined as patients showing stability on both X-rays (delta mTSS [0-52weeks] ≤0) and the functional remission (HAQ ≤0.5), CDAI remission at week 24 increased the likelihood ratio (5.6, patients achieved CDAI remission vs. those did not) of the good outcome at week 52, whereas remission defined by DAS28-ESR, DAS28-CRP, SDAI and Boolean definition did not increased the likelihood ratio. Conclusions: Among remission definition, CDAI at week 24 is an important predictor of good outcome of physical function and bone destruction at week 52 in the patients with RA treated by TCZ. Disclosure of Interest: K. Hanami: None Declared, K. Saito: None Declared, H. Tasaka Employee of: Chugai Pharma, Y. Tanaka Consultant for: Mitsubishi-Tanabe Pharma, Pfizer Inc., Speakers Bureau: Mitsubishi-Tanabe Pharma, Takeda Pharmaceutical Co Ltd, Abbott, Eisai Pharma, Chugai Pharma